The Impact of Connected and Automated Vehicles on Pedestrians (symposia). (December 2017) - Schebesch, Rod; Toop, Erin; Sturges, Dan; Fast, Victoria
Abstract : Background: Imagine you're walking through downtown Calgary and a bus shuttling people from the LRT station to their place of employment approaches. You enter the crosswalk as the countdown is nearing its end. Oncoming traffic knows to pay attention to crosswalks and watch for pedestrians. You notice this shuttle has no driver – its automated. So, does the shuttle know to stop for pedestrian traffic as well as vehicular? This is a question we're all considering as the implementation of CAVs becomes more commonplace. There's a lot of research and testing occurring now to ensure that pedestrians, drivers, and cyclists are safe in a transportation network that is shared with autonomous vehicles. We're on the cusp of a powerful transformation in the way we travel. Aim: Our panelists will discuss the impact that automated vehicles will have on walkability in the near and distant future. We will examine the effects CAVs will have on land planning and community design, which will factor into pedestrian safety. We'll also examine how communities can prepare for CAVs now to enhance walkability once the technology is implemented. Method: Our intent is that the panel will represent perspectives from academia, vehicle manufacturing, and the consulting industry. Each panelist will share their experiences working with CAV technology and information related to the interaction of CAV with pedestrians. Case studies will be presented to demonstrate discussion points. Outcomes: Each participant will walk away with an understanding of the current state of CAV technology and the inherent challenges - and opportunities - in introducing this technology into urban environments.